IMPLEMENTATION OF PULL-SYSTEM USING KANBAN - Shiva Kumar G N, Varadarajan Y S, Basavaraju. G (International Journal of Research Science and Management, 2015)
The fluctuations in demand and customer requirements have made many established companies in improving their manufacturing process by adopting advanced system. One of these systems is PULL SYSTEM, which utilizes KANBAN. This paper deals with implementation of pull system with the use of HUB (WARE HOUSE) WITHDRAWAL KANBAN (HWK) in a leading auto-component supplier for Automobile/Automotive companies in INDIA. The objectives are of two-fold; the first one is to implement pull system and the other is to utilize material handling equipment to best of its use. This case study mainly focussed on 'A' Category items of Ball-pins and Sockets, which are major components of the company. The result showed that customer demand is unpredictable and maintaining inventory in optimal level is difficult task. Pull system is one good tool in maintaining inventory at its optimal level.